Incidence and prevalence of cardiovascular disease in English primary care: a cross-sectional and follow-up study of the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC). Issue 8 (20th August 2018) - Hinton, William; McGovern, Andrew; Coyle, Rachel; Han, Thang S; Sharma, Pankaj; Correa, Ana; Ferreira, Filipa; de Lusignan, Simon
Abstract : Objectives: To describe incidence and prevalence of cardiovascular disease (CVD), its risk factors, medication prescribed to treat CVD and predictors of CVD within a nationally representative dataset. Design: Cross-sectional study of adults with and without CVD. Setting: The Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) is an English primary care sentinel network. RCGP RSC is over 50 years old and one of the oldest in Europe. Practices receive feedback about data quality. This database is primarily used to conduct surveillance and research into influenza, infections and vaccine effectiveness but is also a rich resource for the study of non-communicable disease (NCD). The RCGP RSC network comprised 164 practices at the time of study. Results: Data were extracted from the records of 1 275 174 adults. Approximately a fifth (21.3%; 95% CI 21.2% to 21.4%) had CVD (myocardial infarction (MI), angina, atrial fibrillation (AF), peripheral arterial disease, stroke/transient ischaemic attack (TIA), congestive cardiac failure) or hypertension. Smoking, unsafe alcohol consumption and obesity were more common among people with CVD. Angiotensin system modulating drugs, 3-hydroxy-3-methylglutaryl-coenzyme (HMG-CoA) reductase inhibitors (statins) and calcium channel blockers were the most commonly prescribed CVD medications. Age-adjusted and gender-adjusted annual incidence for AF was 28.2/10 000 (95% CI 27.8 to 28.7); stroke/TIA 17.1/10 000 (95% CI 16.8 to 17.5) and MI 9.8/10 000 (95% CI 9.5 to 10.0). Logistic regression analyses confirmed established CVD risk factors were associated with CVD in the RCGP RSC network dataset. Conclusions: The RCGP RSC database provides comprehensive information on risk factors, medical diagnosis, physiological measurements and prescription history that could be used in CVD research or pharmacoepidemiology. With the exception of MI, the prevalence of CVDs was higher than in other national data, possibly reflecting data quality. RCGP RSC is an underused resource for research into NCDs and their management and welcomes collaborative opportunities.